2004
DOI: 10.1038/labinvest.3700178
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular signal-regulated kinase (ERK) in glucose-induced and endothelin-mediated fibronectin synthesis

Abstract: Increased extracellular matrix protein deposition and basement membrane thickening are important features of diabetic angiopathy. One key matrix protein that has been shown to be instrumental in basement membrane thickening is fibronectin (FN). We have previously demonstrated that glucose-induced increased expression of endothelin-1 (ET-1), may in part, be responsible for increased FN expression via nuclear factor-jB (NF-jB) and activating protein (AP-1) activation. The present study was aimed at elucidating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 33 publications
2
68
1
Order By: Relevance
“…We have also demonstrated that ET-induced fibronectin mRNA production may also be mediated via MAPK signalling [10]. Moreover, the current study and other investigations in the literature indicate that MAPK may influence PKB activation [19,33].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We have also demonstrated that ET-induced fibronectin mRNA production may also be mediated via MAPK signalling [10]. Moreover, the current study and other investigations in the literature indicate that MAPK may influence PKB activation [19,33].…”
Section: Discussionmentioning
confidence: 66%
“…Such molecular changes may arbitrate glucose-induced signals for fibronectin mRNA expression. We have previously demonstrated that mitogen-activated protein kinase (MAPK) and protein kinase C (PKC) may cause fibronectin mRNA and protein upregulation [10]. It is increasingly being realised that such protein kinase pathways may also interact and cross-talk with cellular process regulation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that high glucose levels lead to increased transcriptional upregulation of p300. The signaling mechanisms of this glucose-induced effect were examined following treatment of the endothelial cells to pharmacological inhibitors of signaling pathways known to be altered in diabetes (21,22,24). The results showed that p300 mRNA expression was downregulated by inhibitors of the MAPK, PKC, and PKB pathway (Fig.…”
Section: P300 In Ecm Expressionmentioning
confidence: 99%
“…RNA isolation and cDNA synthesis. Trizol reagent (Invitrogen, Burlington, ON, Canada) was used to isolate total RNA as described (21,22). First-strand cDNA synthesis was performed using Superscript-II system (Invitrogen).…”
mentioning
confidence: 99%
“…Fibronectin expression was shown to increase in an ERK/MAPK dependent manner in endothelial cells following stimulation with high levels of glucose [31].…”
Section: Discussionmentioning
confidence: 99%